Da linguagem e sua relação com o autismo: um estudo linguístico saussureano e benvenistiano sobre a posição do autista na linguagem - Barros, Isabela Barbosa do Rêgo (2011)
The language is a central theme in studies of autism because it implies one of the pillars for the clinical diagnosis of conduct disorder. However, rather than just a diagnostic tool, is the home of the constitution and means of enunciation of the autistic subject. Understanding the relationship between this language and, from the recognition of the place it occupies in the face of language, speech and language, set the goal of this thesis, within the field of linguistic theory based on ideas of Ferdinand de Saussure and the ideas enunciative of Émile Benveniste. The high incidence of theoretical discussions of language in Speech Therapy, marked mainly by the characterization or the observance of its existence or nonexistence in autism, and the scarcity of studies on the different perceptions of autism from the point of view of linguistics, motivated the construction of this thesis. This is characterized as a theoretical study in which cast a look on the structuralist language, they are presented excerpts of two autistic children language by way of illustration in the midst of discussions, showing a peculiar way for the person to relate to language, with language and speech permeated with security between language and subject. We conclude that the autistic subject is fully inserted into the linguistic system of Ferdinand Saussure in a peculiar manner, establishing a more intense relationship with speech due to the objectivity of syntagmatic relations compared to the associative relationships that require exposure of the subject. Thus, establishes an unequal relationship in the language marked by the achievement of extreme positions, attached to the shaft by means of a syntagmatic speech echolalia or loose on the shaft by means of associative neologisms. When we rely on conceptions of Benveniste, we conclude that there are two types of relationship between the individual with autism with speech: a relation of subject-object marked by self-stimulation and security on the object and a relation of subject-language is characterized by through the speech utterance of the subject. These findings led us to consider that there is language in a unique position as a subject of enunciation, where inadequacies in the use of pronouns to the common language of autistic, with the differentiation of "I" and "you", promotes the emergence of the position "him , someone who speaks as the place of enunciation of the autistic subject. This knowledge allows the audiologist to understand the language as something beyond communication and understand the symptoms of autism is, in fact, the only possibility to state the subject is found, therefore, a language feature.